Predictors of Organizational Commitment in Nursing: Results from Portugal - Orgambídez, Alejandro; Almeida, Helena (Investigación y Educación en Enfermería, 2018)
Objective. This work sought to assess the predictor role of work engagement and social support from the supervisor and coworkers on affective commitment with the organization in nursing staff from southern Portugal. Methods. A cross-sectional study was conducted with participation from 215 nursing professionals from three public hospitals in southern Portugal. Results. Of the respondents, 77.21% were women. Statistically significant and positive correlations were observed between affective organizational commitment and the three dimensions of engagement: vigor (r=0.48), dedication (r=0.49), and absorption (r=0.48). Likewise, support from the supervisor and support from coworkers were positively related with affective commitment (r=0.45 and r=0.24, p<0.01). The linear and hierarchical regression model showed the following significant predictors: support from the supervisor (beta=0.28), vigor (beta=0.26), and absorption (beta=0.17). Conclusion. Social support from the supervisor and work engagement (vigor and absorption) are important determinants of the affective bond of nursing professionals with their health organizations. Training and formation of the supervisors in leadership and coaching styles, and labor resources at work would permit increasing the levels of affective commitment in the health units. How to cite this article: Orgambídez A, Almeida H. Predictors of Organizational Commitment in Nursing: Results from Portugal. Invest. Educ. Enferm. 2018; 36(2):e14.